Patron-Client Politics and the 2023 Governorship Election in Enugu State, Nigeria - Udeogu, Celestine Uchechukwu; Nnamani, Vivian Chisom (Covenant University Journal of Politics and International Affairs, 2024)
The study empirically examines the interplay between patron-client politics and the dynamics of the 2023 governorship election in Enugu state, Nigeria. Until the 2023governorship election, political domination and repeated arm-twisting of other political parties by the ruling People’s Democratic Party (PDP) and its extended powerful party machine (the Ebeano political family) almost rendered the state a one-party state since 1999. The objectives of the study are to ascertain whether Peter Mbah’s association with the Ebeano political dynasty contributed to his emergence as both the PDP flag bearer and governor of Enugu state, on the one hand; and to ascertain the role of Peter Obi’s personality cult in the competitiveness of the 2023 gubernatorial election in the state. Utilizing the patron-client theory, the study investigates the manner in which patronage network exerted influence on electoral dynamics and voters’ behaviour during the gubernatorial contest. The mixed methods approach, encompassing qualitative interviews, archival scrutiny, and questionnaire survey analysis, was adopted. The findings show that the Ebeano leaders were not as key to Mbah’s poll victory as they were to his emergence as the party’s flagbearer; and that Peter Obi’s personality cult injected unprecedented competitiveness to the 2023 gubernatorial election in Enugu state. The study recommends mitigating the less desirable effects of patron-client politics and promoting more equitable, transparent and democratic political process in Nigeria through appropriate legislations and emphasis on civic/political education in schools.